Determination of Relative Seed Storage Potential using Natural and Accelerated Ageing in Pea (Pisum sativum L.) - GEETA BASSI; MOHAN SINGH; P.S. BRAR (Seed Research, 2026)
Seeds of five varieties of pea (Pisum sativum L.) viz. Arkel, Matar Ageta 6, Mithi Phali, Punjab-87 and Punjab-88 were subjected to natural vis-a-vis accelerated ageing conditions to predict seed storage potential and relative storage potential of the seeds. Seeds of 'Matar Ageta 6' registered 18 months of storability in terms of maintaining minimum seed certification standards (MSCS) for germination per cent and thus designated as good storer. Whereas variety Arkel was adjudged to be the poor storer as it showed 10 months of seed storage potential under ambient conditions. Seed storability of Punjab 88 was 14 months and that of Mithi Phali and Punjab-87 was 12 months, thus adjudged to be the intermediate storers. Seeds with good/intermediate storability under natural storage conditions could withstand the accelerated ageing even up to 21/14 days. However, increased chronological age rendered seeds more susceptible to accelerated ageing. It was also observed that accelerated ageing of only one day enhanced the germination over control in all the cultivars under study.